Bone health status among postmenopausal women in Malaysia - Nurumal, Mohd Said; Md Isa, Muhammad Lokman; Nik Mohd Hatta, Nik Noor Kaussar; Daud, Azlina; Ibrahim, Muhammad; Sharifudin, Mohd Ariff; Draman, Samsul (Aras Part Medical International Press, 2019)
Objectives: The study has evaluated bone health status among post-menopausal women in a public hospital of Malaysia. Materials and Methods: A total of 116 post-menopausal women, who met the criteria, participated in this study. The purposive sampling method was used to achieve the criteria of participants. Results: This cross-sectional study revealed that more than half of the respondents (52.6%, n=61) had osteopenia; whereas, 47.4% (n=55) of the respondents had osteoporosis. There was a significant correlation between the age and menopausal years with the bone health status (i.e. P=0.004 and P=0.028, respectively) in postmenopausal women. Conclusions: Menopausal women experienced deterioration of bone mineral density (BMD) with advancing age and menopausal